Experimental study on axial compression performance of steel tube confined concrete after freeze-thaw cycles - Zaiping Zeng; Genli Ren (Results in Engineering)
To investigate the axial compression performance of steel tube-confined concrete short columns subjected to freeze-thaw cycles, this study fabricated 30 specimens. Subsequently, axial compression tests were conducted on these specimens after exposure to freeze-thaw cycles. The experimental setup accounted for variations in parameters such as the number of freeze-thaw cycles, concrete strength grade, aspect ratio, and relative slip damage at the interface. The results indicate that, regardless of the presence of relative slip damage at the interface between the steel tube and concrete, the failure mode of the short column remains consistent for a given diameter-to-thickness ratio. Furthermore, it was found that the circumferential constraint coefficient significantly influences the failure mode while exhibiting minimal sensitivity to freeze-thaw degradation. As the number of freeze-thaw cycles increases, there is a notable reduction in load corresponding to the inflection point on the load-lateral deformation relationship curve. Concurrently, although there is an overall slight decrease in longitudinal stress ratios, transverse stress ratios exhibit an increase. To validate the trends regarding how freeze-thaw cycles affect longitudinal and transverse stress ratios, we employed a self-designed program for their calculation.